Productivity, energy prices, and the great moderation: A new link - Rajeev Dhawan; Karsten Jeske; Pedro Silos (Federal Reserve Bank of Atlanta, 2008)
We study how total factor productivity (TFP), energy prices, and the Great Moderation are linked. First we estimate a joint stochastic process for the energy price and TFP and establish that until the second quarter of 1982, energy prices negatively affected productivity. This spillover has since disappeared. Second, we show that within the framework of a dynamic stochastic general equilibrium model, the disappearance of this energy-productivity spillover generates the significantly lower volatility of output and its components. Specifically, the change in the joint stochastic process accounts for close to 70 percent of the moderation in output volatility.
Keywords: C22; E32; Q43; 330; Bayesian estimation; productivity; energy price; Great Moderation; business cycles; Konjunktur; Volatilität; Produktivität; Stochastischer Prozess; Energiepreis; Dynamisches Gleichgewicht; Theorie; USA